Rhododendron maxwellii - Hoo, P.K.; Colin Ruzelion Maycock; Damit, A.; Khoo, E.; Nilus, R.; Sugau, J.; Tanggaraju, S.; Tsen, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Rhododendron maxwellii is restricted to Mount Kinabalu and Mount Tambuyukon, Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 48 km2 and 131.2 km2, respectively and are not in decline. It is found in two distinct mountains within Kinabalu park. The most plausible threats are landslides and climate change which could drive the species to Critically Endangered or Extinct in the near future. Hence, it is assessed as Vulnerable. Rhododendron maxwellii is endemic to Sabah, Malaysia. It is restricted to Mount Kinabalu and Mount Tambuyukon (Argent et al. 2007).